"The Road Not Taken": A Study of Moral Intensity, Whistleblowing, and Regret. Issue 4 (19th May 2019) - Fredin, Amy; Venkatesh, Roopa; Riley, Jennifer; Eldridge, Susan W.
Abstract : Despite attempts to encourage whistleblowing, lingering reluctance to report questionable acts remains frustratingly apparent. Our objective is to examine the regret a professional anticipates when evaluating the action of reporting or not reporting, and whether the framing of the action influences regret. Responses from 263 professionals indicate that regret depends on the moral intensity of the situation and how the action is framed. Regret for whistleblowing is not comparable to regret for not remaining silent, despite the fact that these two descriptions result in the same action. This important implication may inform the way we educate and encourage whistleblowing.